Interconnection of Religion and Culture in the Multicultural Education in Indonesia - Anis, Ahmad; Miftah, Muhammad; Manshur, Ali; Nadiyya, Ahsanu (Jurnal Pendidikan Multikultural Indonesia, 2024)
Education is one of the determinants of character development and the future of the nation. The failure of education in forming character is caused by various social, economic, political, cultural, religious and moral inequalities which cause disharmony in social relations. Religion exists not just as a belief but as an intermediary that makes people know how to relate to God and fellow creatures, so that religion is not only lived and practiced in everyday life, but education must also be able to instill religious and cultural values, so that the multicultural character of students is formed. This research aims to determine the relationship between religion, culture, and education. The type of this research is qualitative research through a literature study approach with analytical techniques through data reduction, data presentation, and descriptive data conclusions from various literature. The object of this study is religion and culture, including definitions, types, elements and relationships between religion and culture. While the subject of this research is educational institutions in Indonesia in multicultural education through various literature. The results of this research show that religion and culture have important values ​​in education. Each has a strong connection to education. Thus, the implications of this research are expected that Indonesian peoplerealize the importance of religion in education because it can strengthen faith, beliefs and morals. The importance of culture in education makes people have life guidelines and obey norms or rules. This research can also increase awareness and appreciation of religious and cultural diversity among students, teachers, and other education stakeholders.